Pemberdayaan Industri Kecil dan Menengah Pakan Ternak melalui Optimalisasi Mesin Pencacah Sorgum - Rini Prasetyani koehkoeh; Renny Reswati; Adhi Mahendra; Sodikun (LOSARI DIGITAL, 2026)
This program aims to develop and optimize a sorghum chopper machine used by Small and Medium Industries (SMIs) as a strategic innovation to support national food security in line with the current government’s Asta Cita agenda. Sorghum is a highly nutritious and promising commodity for alternative livestock feed; however, the chopping process often faces technical issues, particularly during the initial operation of the machine. To address this problem, an additional optional device was engineered to function as a tension adjuster that regulates the tightness of the V-belt connecting the power source and the chopper unit. With this optional device, the machine’s starting process becomes lighter, safer, and more efficient. The research employed design engineering and performance testing methods, with assessment parameters including chopping capacity, fuel consumption, and cut quality. The test results indicated that the optional device successfully reduced the machine’s initial load by up to 35%, improved operational stability, and produced sorghum chops measuring 1–3 cm with an average capacity of 180 kg/hour. This innovation provides a significant contribution to enhancing the efficiency of sorghum-based livestock feed processing for SMIs and supports the national policy direction toward strengthening food self-sufficiency.